(untitled) (Journal of the College of Basic Education, 2023)
The effects of magnetic pretreatment of seeds on growth were studied. Chickpea seeds were used in this work and pretreated with magnetic field (magnetic flux density) B of 2000 gauss for 1, 2 and 3 hours treatment time. After ten days of growth, the average length measured and show clear difference between treated and untreated one. The average length difference between 1, 2 and 3 hours treatment and untreated one are 13.88 cm, 14.67 cm, and 15.721 cm respectively.